Reinvestigating the effect of alcohol consumption on hypertension disease - Kanchit Suknark (2018)
© Springer International Publishing Switzerland 2016. The researchers reinvestigate the effect of alcohol consumption on hypertension from observational data, taken from the Thai National Health Examination Survey. In the observed samples, the treatment assignment is not ignorable, thus using treatment as a dummy variable in the statistical model will lead to the bias estimation of treatment effects. Factors affecting self-selection (drink/not drink) may cause the dummy variable of treatment to be correlated with random errors in the outcome model, which leads to the biased parameters estimation. We propose to use copula-based endogenous switching regression for ordinal outcomes as the more appropriate model for treatment effect estimation. The new results should give us more a accurate and reliable treatment effect for causal inference.